2006
DOI: 10.1007/s00066-006-1485-0
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine Concurrent with Thoracic Radiotherapy after Induction Chemotherapy with Gemcitabine/Vinorelbine in Locally Advanced Non-Small Cell Lung Cancer

Abstract: After induction chemotherapy, the MTD and frequency of gemcitabine in locally advanced NSCLC is 500 mg/m(2) every 2 weeks during a maximum of 7 weeks of thoracic radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…However, their total radiation dose, overall treatment time and MED was in the expected range. The MED, which was according to literature and also in our se- ries highly associated with oesophagitis, was not significantly different between the sequential and concurrent groups [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15]. The incidence and severity of oesophagitis and of neutropenia in the chemoradiation group are also in line with published data [2,3,4,15,19].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, their total radiation dose, overall treatment time and MED was in the expected range. The MED, which was according to literature and also in our se- ries highly associated with oesophagitis, was not significantly different between the sequential and concurrent groups [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15]. The incidence and severity of oesophagitis and of neutropenia in the chemoradiation group are also in line with published data [2,3,4,15,19].…”
Section: Discussionsupporting
confidence: 77%
“…The MED, which was according to literature and also in our se- ries highly associated with oesophagitis, was not significantly different between the sequential and concurrent groups [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15]. The incidence and severity of oesophagitis and of neutropenia in the chemoradiation group are also in line with published data [2,3,4,15,19]. The finding that neutropenia induced by chemotherapy before radiotherapy was not associated with oesophagitis during radiotherapy implies that the correlation between neutropenia and acute oesophagitis during concurrent chemoradiation may be either due to a higher effective bio…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since concurrent RCT leads to a significantly higher rate of side effects, it was concluded that this treatment modality should be reserved only for relatively young patients with few concomitant diseases. In addition to hematotoxicity, the increase in local side effects of radiotherapy (e.g., esophagitis) was a particular problem, even though the intensity of chemotherapy was reduced during irradiation [3,8].Most patients with NSCLC are in poor general health. Our goal was, therefore, to implement a treatment regimen that is practicable in these patients with decreased organ reserve capacity.…”
mentioning
confidence: 99%
“…The outcome of curative treatment of inoperable non-small cell lung cancer (NSCLC) is unsatisfactory with low survival and high local failure rates [7,18,22,35]. This is the reason for the urgent search for new therapeutic options in conservative treatment of NSCLC [8,10,12].…”
Section: Introductionmentioning
confidence: 99%